Long‐term change of total cloud cover and its possible reason over South China during 1960–2012. (18th November 2019) - Fu, Chuanbo; Dan, Li; Lin, Xiaobin; Yang, Fuqiang
Abstract: Long‐term trend of total cloud cover (TCC) had been studied based on 51 meteorological stations across South China during the period 1960–2012. TCC reduction mainly happened over the past 53 years, and the value of climatic trend rate (CTR) averaged in all stations was − 0.625%·10a −1 . The primary cause of the significant reduction of TCC was the temperature (LT) and relative humidity (LRH) in the low troposphere in the context of global warming. Correlation coefficients between TCC and LRH in annual and seasonal mean had all passed 99% significance test, and strong positive correlations indicate that LRH plays a much more important role in the change of TCC in South China. Abstract : Spatial distribution of CTC (a) and temporal variation (b) of all stations averaged annual TCC in South China during1960 to 2012.